Evaluating the impact of curfews and other measures on SARS-CoV-2 transmission in French Guiana - Alessio Andronico (Nature Portfolio, 2021)
Identifying effective combinations of control measures in different populations is important for SARS-CoV-2 control. Here, the authors show that in French Guiana, which has a relatively young population, curfews and localised lockdowns appeared to contribute to reducing transmission.